Looking for Special Education in the Swedish After-School Leisure Program Construction and Testing of an Analysis Model - Peter Karlsudd (Education Sciences, 2020)
How the Swedish after-school leisure program pedagogy relates to special education is rarely the subject of research. The problematization of the special education concept in the after-school leisure centers will be the starting point of this analysis model. This has been constructed with the aim of investigating how actors in the Swedish after-school leisure activities define how special education is being actualized in after school programs. The premises for the study regard the after-school leisure program mission; namely, to complement, compensate, and teach. In order to validate the analysis model, an exploratory pilot study was conducted through interviews with two teacher educators and two teachers in the after-school leisure program. The results show that the models developed for this investigation can be used in further studies. The analysis model provided important key words for further investigation and discussion of the program. These results can in no way be generalized, but they clearly show that the constructed and tested analysis model may form the basis for valuable discussions and pedagogical approaches in teacher education and in the program that the education prepares students for. Therefore, the pilot study comprises the foundation for a more comprehensive future study.